Iran's grand strategy : a political history - Nasr, Seyyed Vali Reza (Princeton : Princeton University Press, 2025)
"Two pervasive fears-of external aggression and internal dissolution-have dominated political discourse and state action in Iran for many decades, and arguably for centuries. This book closely examines these fears, how they've shaped political trends in Iran, and specifically how they have undergirded the conduct of state actors during both the regime of the Shah (the Pahlavi monarchy) of the twentieth century and the Islamic Republic since the 1979 revolution. Drawing on archival sources in the West and in Iran, as well as interviews with key Iranian decision-makers both past and present, Vali Nasr traces this thread of national security through key modern historical episodes in Iran. By viewing modern Iranian history through this lens, Nasr argues that decrying the current Iranian regime as a theocracy is a tired rhetorical move--and inaccurate as an explanation for how it conducts itself in the world. Today's Islamic Republic functions as a modern legal-rational nation-state. It is one that has evolved around a distinct and deeply held view of national interest and national security, rooted in both recent and not-so-recent history. Nasr's book will serve as a corrective to a deeply-rooted view in policy-making circles that the Iranian ruling elite's commitment to Islamic theocracy has driven the country's foreign policy since the time of the revolution"-- Provided by publisher.
"From the New York Times bestselling author of The Shia Revival, a revelatory account of Iran's grand strategy at home and on the world stage. Iran presents one of the most significant foreign policy challenges for America and the West, yet very little is known about what the country's goals really are. Vali Nasr examines Iran's political history in new ways to explain its actions and ambitions on the world stage, showing how, behind the veneer of theocracy and Islamic ideology, today's Iran is pursuing a grand strategy aimed at securing the country internally and asserting its place in the region and the world. Drawing on memoirs, oral histories, and original in-depth interviews with Iranian decision makers, Nasr brings to light facts and events in Iran's political history that have been overlooked until now. He traces the roots of Iran's strategic outlook to its experiences over the past four decades of war with Iraq in the 1980s and the subsequent American containment of Iran, invasion of Iraq in 2003, and posture toward Iran thereafter. Nasr reveals how these experiences have shaped a geopolitical outlook driven by pervasive fear of America and its plans for the Middle East. Challenging the notion that Iran's foreign policy simply reflects its revolutionary values or theocratic government, Iran's Grand Strategy provides invaluable new insights into what Iran wants and why, explaining the country's resistance to the United States, its nuclear ambitions, and its pursuit of influence and proxies across the Middle East"-- Provided by publisher.
Bibliography : pages 339-368.
Keywords: National security -- Iran -- History -- 20th century; National security -- Iran -- History -- 21st century; Iran -- Foreign relations -- 1979-1997.; Iran -- Foreign relations -- 1997.; Iran -- Politics and government -- 1979-1997.; Iran -- Politics and government -- 1997.